Sarcoplasmic reticulum Ca(2+) depletion in adult skeletal muscle fibres measured with the biosensor D1ER - Jiménez-Moreno, Ramón (2010)
The endoplasmic/sarcoplasmic reticulum (ER/SR) plays a crucial role in cytoplasmic signalling in a variety of cells. It is particularly relevant to skeletal muscle fibres, where this organelle constitutes the main Ca(2+) store for essential functions, such as contraction. In this work, we expressed the cameleon biosensor D1ER by in vivo electroporation in the mouse flexor digitorum brevis (FDB) muscle to directly assess SR Ca(2+) depletion in response to electrical and pharmacological stimulation. The main conclusions are: (1) D1ER is expressed in the SR of FDB fibres according to both di-8-(amino naphthyl ethenyl pyridinium) staining experiments and reductions in the Förster resonance energy transfer signal consequent to SR Ca(2+) release; (2) the amplitude of D1ER citrine/cyan fluorescent protein (CFP) ratio evoked by either 4-chloro-m-cresol (4-CmC) or electrical stimulation is directly proportional to the basal citrine/CFP ratio, which indicates that SR Ca(2+) modulates ryanodine-receptor-isoform-1-mediated SR Ca(2+) release in the intact muscle fibre; (3) SR Ca(2+) release, measured as D1ER citrine/CFP signal, is voltage-dependent and follows a Boltzmann function; and (4) average SR Ca(2+) depletion is 20% in response to 4-CmC and 6.4% in response to prolonged sarcolemmal depolarization. These results indicate that significantly depleting SR Ca(2+) content under physiological conditions is difficult.